2020
DOI: 10.1038/s41598-020-78866-2
|View full text |Cite
|
Sign up to set email alerts
|

Rho-GTPase pathways may differentiate treatment response to TNF-alpha and IL-17A inhibitors in psoriatic arthritis

Abstract: Biological therapies have dramatically improved the therapeutic landscape of psoriatic arthritis (PsA); however, 40–50% of patients are primary non-responders with response rates declining significantly with each successive biological therapy. Therefore, there is a pressing need to develop a coherent strategy for effective initial and subsequent selection of biologic agents. We interrogated 40 PsA patients initiating either tumour necrosis factor inhibitors (TNFi) or interleukin-17A inhibitors (17Ai) for activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…59 Of relevance to this study, IL-17 is known to stimulate GTPase activation. 60,61 As shown in our correlation analysis of Patient #3, cytokine IL-17 is connected with several mediators such as IL-12, GM-CSF, IFNg, IL-1β, and TNF-a to exert its proinflammatory effect, also manifested by a robust GTPase signal. Excessive levels of IL-17, such as in Patient # 3 (peak expression on day 6 was 433.0 pg/ml; compared to controls 8.7 ± 11.7 pg/ml 62 ) are comparable to or exceeding levels detected in plasma and tissues during sepsis resulting in multiple organ damage and death.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…59 Of relevance to this study, IL-17 is known to stimulate GTPase activation. 60,61 As shown in our correlation analysis of Patient #3, cytokine IL-17 is connected with several mediators such as IL-12, GM-CSF, IFNg, IL-1β, and TNF-a to exert its proinflammatory effect, also manifested by a robust GTPase signal. Excessive levels of IL-17, such as in Patient # 3 (peak expression on day 6 was 433.0 pg/ml; compared to controls 8.7 ± 11.7 pg/ml 62 ) are comparable to or exceeding levels detected in plasma and tissues during sepsis resulting in multiple organ damage and death.…”
Section: Discussionmentioning
confidence: 74%
“…The significant findings from the analysis of samples from a patient (#3), presenting a robust proinflammatory response, were that the convergence of type1 and type3 response cytokines induced robust downstream GTPase signaling. IL-17, which is known to stimulate GTPase activation; [61,62] was strongly correlated to IL-12, GM-CSF, IFN-g, IL-1β, and TNF-a upstream of a robust GTP loading to Rac1, Rap1, and RhoA. Excessive levels of IL-17, such as in Patient # 3 (peak expression on day 6 was 433.0 pg/ml; compared to controls 8.7 ± 11.7 pg/ml [63]) are comparable to or exceeding levels detected in plasma and tissues during sepsis resulting in multiple organ damage and death.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, differential expression of circulating protein mediators of various immune pathways that correlated with PsA phenotype was reported [ 6 ]. Immunologic heterogeneity was suggested to underlie differences in response to biologic therapies among patients with PsA [ 7 ]. Collectively, these preliminary data support the existence of genetic/immunologic heterogeneity underlying the various PsA disease sub-phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…One study integrated CD4+ T cell transcriptomics with protein data and identified a signaling pathway that strongly associates with IL-17 inhibitor (IL-17i) response. (84) In addition, a recent proof-of-concept study applied machine learning techniques to clinical data and identifi ed patient clusters that follow variable IL-17i response trajectories. (85) This study demonstrates that precision medicine does not necessarily imply using multi-omics, but that application of novel techniques to analyze less complex data can provide relevant insights.…”
Section: … Molecular Biomarkersmentioning
confidence: 99%
“…( 83) BAFF is a cytokine essential for maturation, proliferation and survival of peripheral B cells, and increased circulating BAFF is associated with pSS, SLE and RA. (83,84) In the presence of BAFF, TLR ligation promotes B cell activation, classswitch, somatic hypermutation and plasma cell differentiation that can all promote harmful autoantibody generation. (85)(86)(87) As well as T cells and TLRs, deficiency in the complement system is important to include as a factor contributing to the existence of autoantibodies in AIRD.…”
mentioning
confidence: 99%